Effects of preservatives and drying methods on the nutrient composition and mould counts of hay and pellet processing of Oats - Manlin Wei; Yuxiang Wang; Yufen Zhang; Jinghui Liu; Baoping Zhao; Shiba Lu; Wen Peng; Ming Xiao; Yongjie Zheng (Scientific Reports)
Abstract The aim of this study was to investigate the effects of different preservatives and drying methods on the nutrient composition and mould counts of oat hay and oat pellets. Oat hay and oat pellets were divided into 5 groups: CON (without additives, control), CAP (with 5% calcium propionate), CUR (with 5% curcumin), SKU (with 5% Scutellaria baicalensis) and KC (with 2% potassium carbonate). The nutrients and mould counts of each group were determined after air drying, drying at 50 °C and drying at 50 °C with forced air for 48 h and 96 h, respectively. Compared with air drying, drying at 50 °C and drying at 50 °C with forced air significantly increased the dry matter content of oat. Under different drying times and methods, the addition of preservatives at air-drying for 96 h was more effective at improving the crude protein content of oat hay but was not positive for oat pellets. In addition, under different drying times and methods, the addition of preservatives to oat hay dried at 50 °C for 48 h was more effective at reducing the contents of neutral detergent fibres and acidic detergent fibres. The addition of CUR to oat pellets dried at 50 °C was the most effective at reducing the neutral and acidic detergent fibres of oat pellets. Under different drying times and methods, the addition of preservatives during air drying and drying at 50 °C for 48 h was more effective in reducing mould counts in oat hay and oat pellets. In addition, CUR resulted in higher CP contents and lower mould counts not only in oat hay dried at 50 °C for 48 h but also in oat pellets air dried for 48 h, which indicates its potential use in oat hay production.